The Implementation of Character Education Model at Islamic Boarding School of Pabelan, Magelang, Central Java - Hidayat, Nur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This research was conducted at Islamic Boarding School of Pabelan, Central Java. Here, character education model was delivered to students through role modelling method and formalizing into routines which were implemented since KH. Hamam Dja’far era until now. The implementation of character education developed and taught by Kiai Hamam, as a role model, at that time included model of social caring, direct learning, simplicity, educating humanely, education through role modelling, scientific culture model, development of local wisdom or culture, education development, work ethic, and self-reliance. Then, character values emphasized to student are discipline, work ethic, self-reliance, social caring, spirituality and responsibility.